2014
DOI: 10.1002/2013ja019483
|View full text |Cite
|
Sign up to set email alerts
|

Plasma physics of magnetic island coalescence during magnetic reconnection

Abstract: A large-scale two-dimensional electromagnetic particle-in-cell simulation was employed to study the magnetic island coalescence/merging process during magnetic reconnection with guide field. The merged island after coalescence is characterized by strong core field and plasma density dip at the island center. We found that the core field enhancement is caused by the out-of-plane magnetic field pileup, as well as the field line twisting due to Hall effect. There is an in-plane electric current loop, which is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…J x reaches its peak around B x = 0 without a guide field, while it moves toward the edge of the current sheet in the guide field case. This is consistent with the result of Zhou et al (2014) that the outflow electron jet is deflected away from the neutral sheet as a result of the in-plane Lorentz force. The profile of B y also varies significantly because of the superposition of the guide field.…”
Section: Simulation Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…J x reaches its peak around B x = 0 without a guide field, while it moves toward the edge of the current sheet in the guide field case. This is consistent with the result of Zhou et al (2014) that the outflow electron jet is deflected away from the neutral sheet as a result of the in-plane Lorentz force. The profile of B y also varies significantly because of the superposition of the guide field.…”
Section: Simulation Resultssupporting
confidence: 92%
“…The Hall electromagnetic fields are asymmetric across the current sheet. Zhou et al (2014) identified a super-Alfvénic electron jet extended to 30 s ion inertial length away from the X line in a reconnection region with a weak guide field. This jet was deflected from the neutral sheet owing to the Lorentz force j L × B g ; here, j L is the electric current in the outflow direction and B g is the guide field.…”
Section: Introductionmentioning
confidence: 99%
“…Their typical signatures are an enhancement of the total magnetic field strength and a magnetic bipolar signature (Teh et al, ). In addition, plasma density dips have been reported at their center (Zhou et al, ). The core region is bounded by an electric current loop mainly carried by electrons (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Generally, the plasma density is significantly enhanced in the center of flux ropes [e.g., Khurana et al ., ; Chen et al ., ; Wang et al ., ]. Thus, the occasionally observed density dip within a flux rope [ Retinò et al ., ; and Wang et al ., ] is supposed to be caused by two coalescing flux ropes, as shown in the simulations [ Retinò et al ., ; Zhou et al ., ]. However, if this dip is due to the coalescence, its spatial scale would be thereby comparable to the scales of the flux rope.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Therefore, the magnetic field lines of the two flux ropes can reconnect. Although the coalescence of magnetic flux ropes has been extensively studied by both theories and simulations [ Finn and Kaw , ; Biskamp and Welter , ; Pritchett , ; Oka et al ., ; Zhou et al ., ; Cazzola et al ., ], in situ evidence has not been reported until recently by Wang et al . [].…”
Section: Introductionmentioning
confidence: 99%